Международные стандарты как основа процедуры аудита безопасности приложений - Корниенко, Б.Я.; Юдин, А.К.; Скумен, Ю.Ю. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2010)
In this article we study and analyze the characteristics and the basic procedures
of international standards of information security and their use for security auditing software.